Transformation Leadership Model In Improving The Literature Culture Of Santri In PP Al-Bidayah Jember - Yuliani, Bustanul; Arif, Shaifudin; Kuswoyo, Kuswoyo (Kodifikasia, 2023)
Literacy culture in pesantren is a process of habituation to reading and writing. This activity is a requirement for students as a provision for learning at the pesantren. It takes a strong and visionary transformation paradigm so that it can lead the institution to be born as an institution that has a strong advantage in a particular discipline or field. This kind of indicator was found by the caregivers of the PP Al-Bidayah in Jember in offering a specification of literacy advantages in reading the kitab kuning with various supporting literature. One of the interesting things that the researcher heard and found was the statement he always echoed to the students, namely "read, read, read. Memorize, memorize, memorize." That's a statement that contains the commitment of the caregivers of the PP Al-Bidayah in motivating the students to study hard. The nature of this research is descriptive-qualitative which seeks to provide descriptions of the background, characteristics and distinctive characters in the field. Data in the form of a description of the activities or behavior of the subject and other documents obtained through interviews, observation and documentation. The results of this study indicate that there are several aspects that are emphasized in the transformational leadership model of the Al-Bidayah pesantren caregivers, namely: policy, role model/uswah, learning innovation (implementation of the Al-Bidayah method). Literacy culture can be seen in various daily activities of santri in pesantren, including reading the basic books of the basic theory of nahwu until memorizing; tatbiq activities (analysis of Arabic text by word from the nahwiyyah and shorfiyyah aspects), reading selected nadhoms in the basic theory book for every maktubah prayer, reading nahwiyyah and shorfiyyah dialogue books in every afternoon activity.